2018
DOI: 10.1148/rg.2018170113
|View full text |Cite
|
Sign up to set email alerts
|

J Pouch: Imaging Findings, Surgical Variations, Natural History, and Common Complications

Abstract: Ileal pouch-anal anastomosis, or J pouch, surgery has become the procedure of choice for treatment of medically refractory ulcerative colitis and familial adenomatous polyposis. Overall, this operation is associated with a low rate of postoperative morbidity and good long-term function. However, when complications develop, there is a heavy reliance on imaging to facilitate an accurate diagnosis. Reported postoperative complication rates range from 5% to 35%. Complications generally can be categorized as struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The patient had several complications, which resulted in various symptoms that included incontinence, sleep disruption, fatigue, increased inflammatory markers, fever, and malaise, all of which likely contributed to the reductions in physical activity and reduced overall well-being. Postoperative complications of this nature are fairly common after this procedure, and previous research has indicated that nearly 30% to 45% of patients have postoperative perianal complications, such as incontinence, high frequency of output, abscesses, fistulas [7,14] and pouchitis (in up to 50% of patients) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient had several complications, which resulted in various symptoms that included incontinence, sleep disruption, fatigue, increased inflammatory markers, fever, and malaise, all of which likely contributed to the reductions in physical activity and reduced overall well-being. Postoperative complications of this nature are fairly common after this procedure, and previous research has indicated that nearly 30% to 45% of patients have postoperative perianal complications, such as incontinence, high frequency of output, abscesses, fistulas [7,14] and pouchitis (in up to 50% of patients) [7].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is typically done as a three-step surgical process, which can be completed over several months or years. The second surgery is often considered the most invasive and physically challenging of the three, as this step requires the creation of the anastomosis (J-pouch) and the removal of any remaining colon and rectum [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 Postoperative complications occur in 5% to 35% of the cases, including pouchitis, cuffitis, anastomotic strictures, and leaks, fistulae, and irritable pouch syndrome. 1,4,6 Rates of pouch leaks range from 5% to 18%. 1 The staple or suture lines at the stoma closure site, tip of the "J," pouch body, and pouch-anal anastomosis are common sites for leaks 6,7 which can lead to pouch failure.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,6 Rates of pouch leaks range from 5% to 18%. 1 The staple or suture lines at the stoma closure site, tip of the "J," pouch body, and pouch-anal anastomosis are common sites for leaks 6,7 which can lead to pouch failure. 2,8 Endoscopic therapy has become an effective intervention for structural pouch complications such as strictures, obstructions, fistulae, and leaks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a relatively reliable and widely accepted criterion, the modified pouchitis disease activity index (mPDAI), was created to address this complex issue . To supplement the mPDAI, many studies have focused on finding an innovative and convenient method to indicate pouchitis . The inflammatory nature of pouchitis is usually ignored by researchers.…”
Section: Introductionmentioning
confidence: 99%